Determinants of firm’s effiency : evidence from firms in financial distress / Nazatul Nadia Azman - Azman, Nazatul Nadia (Universiti Teknologi Mara Perlis, 2020)
This study examines the factors affecting efficiency of financially distress firms in Malaysia. The proxy for efficiency is turnover ratio because it is indeed the key to efficiency performance and there are five variables frequently used in previous study to explain differences in turnover ratio. The variables are firm’s size, liquidity, leverage, profitability and working capital. The target population for this paper was all firms listed as financially distressed by Bursa Malaysia under the requirement of Practice Notes 4 (PN4), Practice Notes 17 (PN17) and Amended PN17 (APN17) respectively, from 15 February 2001 when PN4 was introduced, until 31 December2011. The list of all affected issuers was obtained from the Media Releases and Companies Announcement from the Bursa Malaysia website from January 2001 to December 2011. The final sample of firms consists of 190 firms that met the criteria of non-missing data of financial distress costs and other variables, and, therefore, sufficient firm-year observations over the period of five years before financial distress. The five-year period choice is somewhat similar to the study by Bisogno and De Luca (2012). The annual reports of the selected firms were obtained from the Annual companies Handbook (various editions) and the DataStream.